Current practice of usual clinic blood pressure measurement in people with and without diabetes: a survey and prospective ‘mystery shopper’ study in UK primary care - Stevens, S; McManus, RJ; Stevens, RJ (BMJ Publishing Group, 2018)
Objectives: Hypertension trials and epidemiological studies use multiple clinic blood pressure (BP) measurements at each visit. Repeat measurement is also recommended in international guidance; however, little is known about how BP is measured routinely. This is important for individual patient management and because routinely recorded readings form part of research databases. We aimed to determine the current practice of BP measurement during routine general practice appointments. Design: (1) An online cross-sectional survey and (2) a prospective ‘mystery shopper’ study where patients agreed to report how BP was measured during their next appointment. Setting: Primary care Participants: Patient charity/involvement group members completing an online survey between July 2015 and January 2016. 334 participants completed the prospective study (51.5% male, mean age=59.3 years) of which 279 (83.5%) had diabetes. Primary outcome: Proportion of patients having BP measured according to guidelines. Results: 217 participants with (183) and without diabetes (34) had their BP measured at their last appointment. BP was measured in line with UK guidance in 63.7% and 60.0% of participants with and without diabetes, respectively. Initial pressures were significantly higher in those who had their BP measured more than once compared with only once (p=0.016/0.089 systolic and p<0.001/p=0.022 diastolic, in patients with/without diabetes, respectively). Conclusions: Current practice of routine BP measurement in UK primary care is often concordant with guidelines for repeat measurement. Further studies are required to confirm findings in broader populations, to confirm when a third repeat reading is obtained routinely and to assess adherence to other aspects of BP measurement guidance.